Primary School Pupils’ ICT Literacy in Northern Aegean - Panagiotis, Giavrimis; Nikolarea, Ekaterini (Mediterranean Journal of Social Sciences, 2012)
The present research is part of the outcomes of a wider research that explores the ICT [Information CommunicationTechnology] applications to Greek Public Primary Schools and their impact on teaching, learning and cognitive processes aswell as on pupils’ behavioural adaptation, according to Primary Education Teachers’ opinions and the Pupils of the 5th and 6thGrades of Greek Public Regular and Day-long Primary School (DLPS). The research sample consisted of 316 pupils, of the 5thand 6th Grades of (Public) Primary Schools in Northern Aegean. Of the pupils, 153 (48.4%) were boys and 163 (51.6%) weregirls. In the outcomes, it is discussed about pupils’ opinions on the degree of their acquisition of basic ICT skills, as mentioned inthe Greek Primary School Curriculum.